Kepuasan Pelanggan sebagai Kunci: Pengaruh Kualitas Produk dan Presepsi Harga terhadap Loyalitas Pelanggan Dimsum Uma Yum Cha Pasar Gede Solo - Hanafi, Charlestiana Leta; Zahra, Avida; Swari, Kharisma Isna; Elvana, Fausta Fika Deas (Journal of Economics and Business Research (JUEBIR), 2024)
The purpose of this study is to see how perceptions of price and product quality impact customer satisfaction and customer loyalty. at Dimsum Uma Yum Cha.. This research uses quantitative methodology with purposive sampling technique and the sample taken was 171 respondents. Data was collected through questionnaires and tested using validity, reliability, and hypothesis testing analysis to determine the independent variables (product quality and price perception) as the dependent variable (customer loyalty) with customer satisfaction as the mediating variable. The impact is assessed from the research results which show that product quality and price perception have a significant influence on customer satisfaction. In addition, customer satisfaction also has a significant influence on customer loyalty. This can increase customer satisfaction by maintaining product quality and reasonable price perceptions, which in turn has an impact on Uma Yum Cha's customer loyalty even in the midst of intense competition, that's the proof